The Effect Of Price Perception And Promotion On Consumer Satisfaction Of Gojek Online Transportation Service Users In The City Of Tasikmalaya - Kiki Wulansari; Ari Arisman Ari Arisaman; Barin Barlian Barin Barlian (Jurnal Manajemen Bisnis Eka Prasetya, 2022)
This study aims determine and analyze the effect price perception and promotion partially and simultaneously on consumer satisfaction at gojek online transportation user Tasikmalaya City. The method used in this reseach is quantitative method with a consumers survey approach with a sample of 100 respondents. Data collected in the form of data is carried out using a qustionnaire technique. Data analysis in this survey uses multiple regression analysis, correlation coefficient determination using SPSS software. The results of the survey that the price perception and promotion simultaneously and partially have a significant on consumer satisfaction.